Historical methodological aspect of labour market conception - Šileika, Algis; Andriušaitienė, Daiva (Business: Theory and Practice, 2007)
What is the commodity in the labour market – labour force, labour or labour services? What is the labour market? What is the difference between labour force market and labour resources market? Rather frequent confusion of these conceptions (even in scientific literature) shows that these conceptions are not clearly conceptually determined. The article indicates that not labour force but labour – functional status of labour force - is purchased in the market. Namely labour is the main object of labour demand and supply. All relations with labour market subjects focus on hiring relations and these become the main conditioning element. Thus when designing the measures of labour market policy and looking for their improvement, it is important to remember that driving forces as well as “short” places of essential factors determining the working of economic mechanism focus namely on hiring relations. Article in Lithuanian. Istorinis metodologinis darbo rinkos sampratos aspektas Santrauka. Kas yra prekė darbo rinkoje – darbo jėga, darbas ar darbo paslaugos? Kas yra darbo rinka? Kuo skiriasi sąvokos darbo jėgos rinka ir darbo išteklių rinka? Tai, jog šios sąvokos nepakankamai aiškiai konceptualiai apibrėžtos, rodo pernelyg dažnas jų painiojimas – netgi mokslinėje literatūroje. Straipsnyje motyvuojama, kad rinkoje perkama ne darbo jėga, o darbas – funkcinė darbo jėgos būsena. Būtent darbas yra pagrindinis darbo rinkoje besiformuojančios darbo paklausos ir pasiūlos objektas. Visi darbo rinkos subjektų santykiai fokusuojami samdos santykiuose, kurie tampa pagrindiniu ją pačią formuojančiu elementu. Reikšminiai žodžiai: darbo jėga, darbas, darbo rinka, samdos santykiai.